Assessment of the effectiveness of surgical resections following tyrosine kinase inhibitor therapy in patients with EGFR-mutated stage III–IV lung adenocarcinoma - E. V. Levchenko; F. V. Moiseenko; S. V. Orlov; E. N. Imyanitov; A. E. Mikhnin; M. L. Gelfond; E. N. Slugin; S. M. Ergnyan; N. E. Levchenko; A. S. Zhabina; A. M. Ulitin; O. Yu. Mamontov; et al. (Сибирский онкологический журнал)
Objective. To assess the overall and disease-free survival rates in patients with EGFR-mutated lung adenocarcinoma, who underwent surgery after achieving the objective response to tyrosine kinase inhibitor (TKI) therapy.Material and Methods. The overall and disease-free survival rates were analyzed in 18 patients with EGFR-positive lung adenocarcinoma, which was inoperable at presentation due to locally advanced disease or the evidence of distant metastasis. In accordance with the clinical standards, patients were recommended for TKI therapy. Surgical resection was performed after achieving the objective tumor response to TKI therapy. The control group included 23 patients with EGFR mutation-positive lung adenocarcinoma, who did not undergo surgery after receiving TKI therapy.Results. The study revealed a statistically significant effect of surgical resection on the overall survival (OS) in patients with EGFR mutation-positive stage III–IV lung adenocarcinoma after response to TKI therapy (p=0.004). However, there was no statistically significant effect on the disease-free survival (DFS) (p=0.40). There was a tendency to increase in the median OS in patients of the study group (46 months) compared to that in patients of the control group (26 months). Surgery in the study group was characterized with some technical difficulties associated with severe fibrosis. However, this did not affect the duration of surgery and the volume of blood loss.Conclusion. Tumor resection in patients with EGFR mutation-positive stage III–IV lung adenocarcinoma is feasible and safe, but requires highly qualified team surgeons in well-equipped medical centers. Our study revealed that the combination of EGFR-TKI and tumor resection provided better PFS and OS than EGFR-TKI alone. However, further studies are required.